If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -6y + -4x + 8y = 0 Reorder the terms: -3x + -4x + -6y + 8y = 0 Combine like terms: -3x + -4x = -7x -7x + -6y + 8y = 0 Combine like terms: -6y + 8y = 2y -7x + 2y = 0 Solving -7x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -7x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 -7x + 0 = 0 + -2y -7x = 0 + -2y Remove the zero: -7x = -2y Divide each side by '-7'. x = 0.2857142857y Simplifying x = 0.2857142857y
| 3x+21=0 | | 5b-2=2(3b-4) | | 141-2x=6x+21 | | y=9+x | | 0.33k-4=9 | | 0.3k-4=9 | | 2d+24-14=84 | | 11x-7=7x+3 | | 11x-9=7x | | 12-(-8x)+2x-(-9)= | | 3(3+4x)=15x | | 5+6x=29 | | 45-7x=3 | | 3(x+3)-4(x-1)=6 | | y=36.76+-3424.731GLO | | 8p+14=2p-22 | | y=86.010*LOG(34-16)-70.041*LOG(71)+36.76 | | m+10m= | | 5n-7=8n-19 | | 5-4=3b-5 | | 25x^2+144=0 | | 0=4+35t-16t^2 | | 3x=2(x-1) | | 5-2x=3-4x+13 | | 21x=20x+16 | | 2a*2a*2a*2a= | | 2a*2a*2a= | | 7x+4y=21 | | 2a*2a= | | -4(-25+5(7+1))=x | | 8.3(x+3)=14 | | 3(x-3)+1=1 |